ChemInform Abstract: Three New Iridoid Glycosides from the Fruit of Gardenia jasminoides var. radicans. Issue 16 (22nd April 2014) - Qin, Fang‐min; Meng, Ling‐jie; Zou, Hui‐liang; Zhou, Guang‐xiong
Abstract isolation and structure elucidation